If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(x + 3) = 9 Reorder the terms: 2x(3 + x) = 9 (3 * 2x + x * 2x) = 9 (6x + 2x2) = 9 Solving 6x + 2x2 = 9 Solving for variable 'x'. Reorder the terms: -9 + 6x + 2x2 = 9 + -9 Combine like terms: 9 + -9 = 0 -9 + 6x + 2x2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -4.5 + 3x + x2 = 0 Move the constant term to the right: Add '4.5' to each side of the equation. -4.5 + 3x + 4.5 + x2 = 0 + 4.5 Reorder the terms: -4.5 + 4.5 + 3x + x2 = 0 + 4.5 Combine like terms: -4.5 + 4.5 = 0.0 0.0 + 3x + x2 = 0 + 4.5 3x + x2 = 0 + 4.5 Combine like terms: 0 + 4.5 = 4.5 3x + x2 = 4.5 The x term is 3x. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3x + 2.25 + x2 = 4.5 + 2.25 Reorder the terms: 2.25 + 3x + x2 = 4.5 + 2.25 Combine like terms: 4.5 + 2.25 = 6.75 2.25 + 3x + x2 = 6.75 Factor a perfect square on the left side: (x + 1.5)(x + 1.5) = 6.75 Calculate the square root of the right side: 2.598076211 Break this problem into two subproblems by setting (x + 1.5) equal to 2.598076211 and -2.598076211.Subproblem 1
x + 1.5 = 2.598076211 Simplifying x + 1.5 = 2.598076211 Reorder the terms: 1.5 + x = 2.598076211 Solving 1.5 + x = 2.598076211 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = 2.598076211 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = 2.598076211 + -1.5 x = 2.598076211 + -1.5 Combine like terms: 2.598076211 + -1.5 = 1.098076211 x = 1.098076211 Simplifying x = 1.098076211Subproblem 2
x + 1.5 = -2.598076211 Simplifying x + 1.5 = -2.598076211 Reorder the terms: 1.5 + x = -2.598076211 Solving 1.5 + x = -2.598076211 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = -2.598076211 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = -2.598076211 + -1.5 x = -2.598076211 + -1.5 Combine like terms: -2.598076211 + -1.5 = -4.098076211 x = -4.098076211 Simplifying x = -4.098076211Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.098076211, -4.098076211}
| y^3-4y^2=0 | | 3(-2-x)=18 | | 7/8*6/5 | | 9m+24= | | 1/2w+7=2w-2 | | 27x-4=9x+2 | | x(x)-5+2forx=6 | | 2-4r=-14 | | 64x^3-49x=0 | | 2n=2n-1 | | 3t+2+2t=-53 | | x(x)-5+12= | | 5x^3+3x^2=125x+75 | | 8/11-2x=-2x+6/11 | | 5x^3/4+2=42 | | 29-5g+3=-3g+6g | | y+2=10 | | 32x-1/5=4 | | 3x-1/5=20 | | .2n-.594=3.5n+9.0 | | -.389y-.974=6.789y | | -3(2x-3)+15=9 | | 5(2x-6)=3(x+4) | | 15-(3m+7)=5+4m-18 | | 2x^2-10=20 | | 8y-6=7y+3 | | x/5+3=5 | | x/5-3=5 | | 6x+5x+15=180 | | 5x^2=24+2x^2 | | x=(1/2) | | 11/16n-3+1/4n=74 |